Nasal colonization of methicillin-resistant Staphylococcus aureus in HIV-infected patients at the Cape Coast Teaching Hospital, Ghana - Boison, Daniel; Akwetey, Samuel Addo; Osei, Silas Acheampong; Kelechi, Samuel; Barnie, Prince Amoah (Frontiers in Tropical Diseases, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) continues to be associated with outbreaks in communities (CA-MRSA) and hospitals (HA-MRSA). MRSA isolates are known to be resistant to all beta-lactam antibiotics including methicillin. Moreover, HIV-infected individuals are highly at risk of CA-MRSA due to their weaker immune system. It is therefore important to keep surveillance of the prevalence. Our study aims at determining the prevalence of Staphylococcus aureus and MRSA among HIV-infected participants, the bacteria’s associations, and their antibiotic susceptibility patterns. A cross-sectional study was conducted and nasal swabs from 657 participants attending the HIV clinic at the Cape Coast Teaching Hospital were taken following guidelines. Confirmed S. aureus isolates were taken through antibiotic susceptibility tests per the Kirby–Bauer method, and isolates that were resistant to cefoxitin were considered to be MRSA. The carriage prevalence of S. aureus and MRSA was 44.7% and 8.2%, respectively, among the HIV-infected individuals. There was a significant association between hospitalization and MRSA colonization (p = 0.002), but not S. aureus colonization (p = 0.266). Significant association was also observed between age (p = 0.001), sex (p = 0.0001), and S. aureus colonization. Similarly, differences in age groups (p = 0.001), sex (p = 0.02), and MRSA colonization were statistically significant (p = 0.001). High percentage resistance was exhibited by the isolates to most of the antibiotics. However, this study did not record vancomycin resistance among the MRSA strains. The study showed high colonization of S. aureus and MRSA in HIV-infected patients, which was mostly associated with the age and sex of the individuals.